2013
DOI: 10.1093/humrep/det306
|View full text |Cite
|
Sign up to set email alerts
|

Cycle cancellation and pregnancy after luteal estradiol priming in women defined as poor responders: a systematic review and meta-analysis

Abstract: NIH K12 HD063086 (ESJ, MGT), NIH T32 HD0040135-11 (KAR), F32 HD040135-10 NIH (KRO), 5K12HD000849-25 (PTJ). No competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 26 publications
(44 reference statements)
3
43
1
5
Order By: Relevance
“…[66] в 2013 г. В него вошли 8 ис-следований: 7 ретроспективных и 1 рандомизируе-мое контролируемое исследование. Во всех исследо-ваниях был использован протокол стимуляции с ан-тагонистами.…”
Section: эстрогенный праймингunclassified
“…[66] в 2013 г. В него вошли 8 ис-следований: 7 ретроспективных и 1 рандомизируе-мое контролируемое исследование. Во всех исследо-ваниях был использован протокол стимуляции с ан-тагонистами.…”
Section: эстрогенный праймингunclassified
“…33 Furthermore, a meta-analysis looking at GnRH antagonist cycles with and without estradiol pretreatment found that there were fewer cancellations and a higher chance of clinical pregnancy with luteal estradiol pretreatment. 35 Estradiol patch luteal priming may be a method to improve IVF cycle outcomes in poor responders, but there is a need for more randomized controlled trials to address this question.…”
Section: Follicular Synchronization Using Transdermal Estrogenmentioning
confidence: 99%
“…Various protocols have been given for improving outcomes for patients with poor responders, but the results are often disappointing, since any given protocol provides the end result with no significant different [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Poor response patient in the literature have diversity in terminology, characterized generally these patients respond minimal to the protocol of ovarian stimulation given, which is illustrated by the results of the low number of follicles, the low number of oocytes, the high failure cycle, in which will ultimately result in lower pregnancy success rates [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation